Glycemic Control and Satisfaction During Ramadan in Patients with Type 1 Diabetes Treated with an Advanced Hybrid Closed Loop Insulin Pump (The Review of Diabetic Studies, 2023)
Background: The closed loop insulin pump has significantly transformed the management of type 1 diabetes since its introduction. Several recent studies have examined the effects of Ramadan fasting on individuals with type 1 diabetes who use closed-loop insulin pumps. These studies have demonstrated that fasting throughout Ramadan leads to an increase in the amount of time spent within the target blood glucose range, while also reducing the occurrence of both hypoglycemia and hyperglycemia. Additionally, fasting has been found to enhance safety and flexibility in managing diabetes during this period. Objective: This study aims to assess the efficacy, safety, and patient satisfaction of the MiniMedTM 780G advanced hybrid closed loop system in managing glycemic control among individuals with Type 1 diabetes throughout the period of Ramadan fasting. Case presentations: Two cases of type 1 diabetes patients who underwent treatment with the MiniMedTM 780G advanced hybrid closed loop device and observed fasting during the month of Ramadan in 2023 were documented. The glycemic target was established at a level of 110 mg/dl, with the potential implementation of a temporary objective if blood glucose levels fell below 100 mg/dl. These parameters enabled the maintenance of optimum glycemic control, with a time in range exceeding 85%, while avoiding an increase in hypoglycemia occurrences and resulting in higher levels of satisfaction. Conclusion: The concept of a closed loop refers to a system in which the output of a process is sent back into the system as input, The utilisation of insulin pump therapy has demonstrated reliability and efficacy in individuals with type 1 diabetes mellitus who observe Ramadan fasting, provided that it is employed accurately. Enabling appropriate glycemic management to enhance quality of life. We present the initial assessment of glycemic control and satisfaction throughout the fasting period of Ramadan using an advanced hybrid closed loop approach, based on the current body of knowledge.